The Effect of the Neuromuscular, Strength, and Combined Training on Balance and Performance in Female Basketball Players - Negar Kooroshfard; Zahra Rahimi (Physical Treatments, 2022)
Purpose: This investigation aimed to compare the effect of neuromuscular, strength, and combined training on dynamic balance and sports performance, including power, sprint, and agility in female basketball players. Methods: In this semi-experimental study, 42 female professional basketball players (age: 19-25 years) were assigned to three groups of Neuromuscular (NM), Strength (ST), and Combined training (CM), and one control group. The Multivariate Analysis of the Variance (MANOVA) was used to compare between-groups data. Dynamic balance and performance measurements (vertical jump, agility, and sprint) of athletes were assessed before and after six weeks of intervention by Star Excursion Balance Test (SEBT), Sargent vertical jump device, Shuttle Run device, and sprint 27-meter test. Results: Results of the MANOVA showed all between-group differences for dynamic balance, sprint, and agility were only significant between the control group and NM, ST, and CM groups (P≤0.05). In addition, the CM group was significantly different compared to the NM and ST groups (P≤0.05). Balance and high jump within-group differences showed a significant increase in the NM, ST, and CM groups in the high jump variable (P≤0.05). For sprint and agility, within-group results showed a significant decrease in the NM, ST, and CM groups (P≤0.05). Besides, the larger effect size was seen in the combined group for all variables. Conclusion: It seems that neuromuscular, strength, and combined training is similarly effective in improving the balance and functional performance of female basketball athletes and there is not a significant difference between them.